Curcumin compounds and total microorganisms in turmeric kombucha as a potential therapy in rats obesity model - Nisa', Zulfia Rosyidatun; Jusuf, Sinu Andhi; Yudhani, Ratih Dewi (Alma Ata University Press, 2025)
ABSTRAKLatar belakang: Prevalensi obesitas meningkat signifikan dalam satu dekade terakhir dan berisiko menimbulkan berbagai komplikasi seperti diabetes melitus tipe 2, kardiovaskular, bahkan kanker. Terapi farmakologi obesitas seperti liraglutide dan orlistat dapat memberikan efek negatif pada tubuh seperti gangguan saluran pencernaan. Hal ini mendorong pengembangan terapi berbahan alami untuk obesitas. Kombucha dan kunyit kuning secara tunggal dilaporkan bersifat antioksidan dan mampu memperbaiki obesitas. Kombinasi kombucha kunyit kuning berpotensi dikembangkan sebagai minuman probiotik untuk obesitas karena senyawa bioaktif yang dikandungnya. Namun, eksplorasi fitokimia dan mikroorganisme pada turmeric kombucha masih sangat terbatas dan penelitian kombinasi kombucha kunyit kuning untuk obesitas belum pernah dilakukan sebelumnya.Tujuan: Mengeksplorasi kandungan fitokimia dan total mikroorganisme kombucha kunyit kuning dan kemampuannya untuk memperbaiki obesitas. Metode: Eksperimental laboratorik dengan rancangan pre-post control group dan deskriptif observasional. Analisis kurkumin menggunakan KLT Densitometri. Mikroorganisme dianalisis dengan metode pour plate kemudian dihitung berdasarkan total plate count. Tikus model obesitas diberikan tiga variasi dosis kombucha kunyit kuning selama 28 hari dan dilakukan penilaian perubahan indeks Lee yang diuji statistik menggunakan Kruskal Wallis (p<0.05) dan Post hoc Dunn Test. Hasil: Hasil penelitian menunjukkan kandungan kurkumin pada kombucha kunyit kuning sebesar 0,73 mg/L dan total mikroorganisme sebesar 2,60 x 107 CFU/ml. Kombucha kunyit kuning memperbaiki indeks Lee tikus model obesitas dibanding kontrol negatif (p<0.05) dengan dosis paling efektif sebesar 4,4 ml/200 g/hari (dosis tertinggi di penelitian ini). Kesimpulan: Kombucha kunyit kuning memiliki kandungan kurkumin dan manfaat mikoorganisme yang dapat memperbaiki indeks Lee pada tikus model obesitas. Kata Kunci: kombucha kunyit kuning; kurkumin; mikroorganisme; obesitas ABSTRACT Background: The prevalence of obesity has increased significantly in the last decade, raising the risk of complications such as type 2 diabetes, cardiovascular diseases, and even cancer. Pharmacological therapies for obesity, such as liraglutide and orlistat, can have negative effects on the body, including gastrointestinal disorders. This drives interest in the development of natural-based therapies for obesity. Kombucha and turmeric individually are known for their antioxidant properties and their ability to address obesity. The combination of turmeric kombucha has the potential to be developed as a probiotic drink for obesity due to the bioactive compounds it contains. However, research into the phytochemical profile and microorganisms in turmeric kombucha is still limited, and no studies have been conducted on the combination of turmeric kombucha for obesity treatment.Objectives: To explore the phytochemical content and total microorganisms in turmeric kombucha and to evaluate its potential in improving obesity treatment.Methods: Laboratory experiments were conducted with pre-post control group design and descriptive observational analysis. Curcumin levels were analysed using KLT Densitometry, while microorganisms were identified through the pour plate method and quantified via total plate count. Obese model rats received three different doses of turmeric kombucha over 28 days, and changes in their Lee index value were assessed and statistically analysed using Kruskal Wallis (p<0.05) and Post hoc Dunn Test. Results: The findings revealed that the curcumin concentration in turmeric kombucha was 0.73 mg/L and the total microorganisms were 2,60 x 107 CFU/ml. Kombucha yellow turmeric improved the Lee index of obese model rat compared to negative control (p<0.05) with the most effective dose being 4.4 ml/200 g/day (the highest dose in this study).Conclusions: Turmeric kombucha contains curcumin and beneficial microorganisms, which can improve the Lee index in obese model rats.Keywords: curcumin; obesity; microorganisms; turmeric kombucha Received: 17 Jan 2025; Revised: 20 Sep 2024; Accepted: 26 Jan 2025; Available online: 30 Mar 2025; Published: 30 Mar 2025